Analasis Yuridis Perjanjian Gadai di PT Pegadaian (Persero) Cabang Maros - Arfah; Payung, Otniel (Jurnal Delik ADPERTISI, 2024)
The main problem of this research is how to analyze the juridical pawn agreement at PT Pegadaian (Persero) Maros Branch. The subject matter is further broken down into several subproblems, namely how to implement the lien agreement at PT Pegadaian (Persero) Maros Branch and how the process of resolving the default of the lien agreement at PT Pegadaian (Persero) Maros Branch. This research is a type of qualitative field research. This research will be conducted by interviews with branch leaders, employees of PT Pegadaian (Persero) Maros Branch and customers of PT Pegadaian. This research uses a sociological legal approach, namely direct field research. Data collection is obtained from observation, interviews and questionnaires. Based on the results of the study, it was answered that the implementation of the pawn agreement at PT Pegadaian (Persero) Maros Branch has not been effective because there are still many customers who do not heed the implementation of the pawn agreement so that only 57% is carried out and the implementation of the lien agreement is not carried out 43% of the total percentage of 100%. Meanwhile, the process of resolving the default of the pawn agreement at PT Pegadaian (Persero) Maros Branch is 1) for customers who do not pay credit installments or maturity, PT Pegadaian will reprimand customers by calling, SMS, writing to customers and the last resort taken is by parate execution or auction, 2) regarding the provision of compensation for lost customer collateral by indemnifying them in full or in whole while damaged collateral can be done by paying compensation of 125% of the estimated value of goods listed in SBK or can be more in accordance with the agreement and policy of PT Pegadaian it self.